Implementation and Effectiveness of Financial Literacy in Higher Education Institutions: A Systematic Literature Review - Agus Sudono; Suryana Suryana; Heny Hendrayati; Chairul Furqon (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study assesses the implementation and effectiveness of financial literacy education at the higher education level to inform the development of appropriate strategies for its integration in university curricula. Methodology: Through a systematic literature review using PRISMA methodology, this study investigates the implementation and effectiveness of financial education in universities and colleges. This research examined 127 peer-reviewed articles from leading international journals that were indexed in Scopus and Web of Science databases, documenting research on financial literacy in university contexts between 2015 and 2025 Main Findings: The study demonstrates that financial literacy education differs significantly among universities and has not been uniformly implemented across various academic fields. Economic, business, and finance are the primary areas of focus in financial education applications; however integration into humanities, science, engineering, etc. is minimal Novelty/Originality of this study: Higher education stakeholders and the public can find the right position on how financial literacy should be implemented at the higher education level. Based on this knowledge, universities can design effective programs and curricula related to financial literacy content in higher education.